The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/bi026711m
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and Sequence Specificity of DNA Binding and Site Selection for Primer Synthesis by Escherichia coli Primase

Abstract: Primase is an essential DNA replication enzyme in Escherichia coli and responsible for primer synthesis during lagging strand DNA replication. Although the interaction of primase with single-stranded DNA plays an important role in primer RNA and Okazaki fragment synthesis, the mechanism of DNA binding and site selection for primer synthesis remains unknown. We have analyzed the energetics of DNA binding and the mechanism of site selection for the initiation of primer RNA synthesis on the lagging strand of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…Our previous studies have indicated that, in the absence of DnaB helicase, primase binds to DNA in a sequential dimer pathway without forming a true dimer (41). We observed a very negligible change in the anisotropy when the primase was added to Ru[bipy] 3 -primase, which supported either a very weak or no direct interaction between primase monomers.…”
Section: Analysis Of In Vitro Primer Synthesis Carried Out By Primasesupporting
confidence: 53%
See 1 more Smart Citation
“…Our previous studies have indicated that, in the absence of DnaB helicase, primase binds to DNA in a sequential dimer pathway without forming a true dimer (41). We observed a very negligible change in the anisotropy when the primase was added to Ru[bipy] 3 -primase, which supported either a very weak or no direct interaction between primase monomers.…”
Section: Analysis Of In Vitro Primer Synthesis Carried Out By Primasesupporting
confidence: 53%
“…Our previous studies on primase-ssDNA binding demonstrated that it associates with DNA as a pseudo dimer (41). However, these studies were carried out in the absence of DnaB and did not preclude the possible formation of a higher order complex.…”
Section: Stoichiometry Of the Complex [Primase-dnab Hexamer] Ismentioning
confidence: 99%
“…In addition, DnaB also modulates primer synthesis in a manner independent of its translocation ability. It relaxes the specificity of the primase, stimulates its activity, and reduces the length of primers to between 10 and 14 nucleotides (1,7,8,10,24). Given the striking differences in the stability of the B. stearothermophilus DnaB-DnaG complex, it is not clear whether these observations apply only to E. coli.…”
mentioning
confidence: 99%
“…The E. coli DnaG gene product is the model eubacterial primase because its structure and function have been extensively characterized. It has been demonstrated that the E. coli primase is slow (9), has low-fidelity (9), binds G4-ori ssDNA as a dimer (10,11), and that DnaB helicase stimulates its catalytic activity over 15-fold (12 Recently, it was demonstrated that the primases and replication fork helicases from mesophilic S. aureus and thermophilic Geobacillus stearothermophilus have properties that diverge from their E. coli homologs (14,15). Both primases initiated from 5'-TTA-3' and 5'-CTA-3'.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%